Is wildlife research useful for wildlife conservation in the tropics?: A review for Borneo with global implications - Meijaard, E.; Sheil, Douglas (2007)
The urgency of the tropical biodiversity crisis continues to be a major justification for wildlife research and its funding. To examine the benefits of this research for on-the-ground conservation, we focused on Borneo, where conservation has a long history and we have direct experience. We compiled, categorized and evaluated 284 publications from a broad variety of sources, 153 from peer-reviewed journals. We found that few studies address threats to species and fewer still provide input for or guidance to effective management. We consider various reasons for these shortcomings. Research is seldom judged on its relevance to pragmatic problem solving. Furthermore, many research programs lack the necessary long-term vision and organizational structure for useful applied research. We consulted conservation leaders about our conclusions and all responses suggest that our concerns are not unique to Borneo but reflect wider problems. We conclude that conservation research across most of the tropics is failing to address conservation needs. We make a number of recommendations based on our findings. Conservation biologists should place a higher priority on addressing practical conservation needs and goals.